Kedudukan Indonesia Dalam Menyikapi Penyelesian Sengketa Internasional Di Laut Cina Selatan - Antonia Immaculata Putri Seran; Bernadus Febriyanto; Yohanes Arman; Pregrinus Rangga (Student Scientific Creativity Journal, 2023)
The conflict that occurred in the South China Sea (LCS) becameflash point in the Asia Pacific region. Disputes in the South China Sea involve not only 6 or even 10 countries, but also involve other major powers such as the United States. The six (6) countries referred to are China, Taiwan, Vietnam, the Philippines, Brunei Darussalam, Malaysia, and (4) four other countries namely Cambodia, Singapore, Thailand and including Indonesia. In its development, the South China Sea (LCS) conflict has also started to "drag" Indonesia since 2010, after China claimed the northern territory of the Natuna Islands, Riau Islands Province which is Indonesia's Exclusive Economic Zone (ZEE). This research is normative juridical law research which includes research on international agreements, research on legal systematics, research on international law, research on the level of legal synchronization. Indonesia is not asclaimant state in the South China Sea dispute, however, Indonesia has national interests in the South China Sea, especially in defending territorial sovereignty in the North Natuna Sea. In its position as a neutral country, Indonesia has played a role in resolving international conflicts in the South China Sea by making various diplomatic efforts by sending protest notes to China and rejecting China's claims of control of the territory it claims to be.traditional fishing ground because it has no basis in international law and the waters of the North Natuna Sea on the basis ofninedash line who have violated Indonesia's ZEE.